التربية الجمالية في العلاقة التكاملية بين الأسرة الحضرية والمدرسة الجزائرية (دراسة ميدانية استكشافية على عينة من الأسر الحضرية بتلمسان) - سيفي, محمّد بدر الدّين (Changement Social, 2019)
تتناول هذه الورقات مسألة (التربية الجمالية) كمجال من مجالات تربية الطفل المتمدرس، ورصد التمثلات الوالدية حول تمظهرات الذوق الجمالي في البيت الأسري وداخل الحياة المدرسية، ومحاولة الكشف عما نجهله من ممارسات يومية داخل المدرسة وتحليلها سوسيولوجيا من خلال ربط هذا المجال بالتغاير النسقي في أنماط الأسرة التربوي، ومدى أهمية هذا المجال التربوي (المجال الجمالي) كجزء وظيفي في طبيعة العلاقة التكاملية بين (الأسرة الحضرية) و(المدرسة كمؤسسة للتنشئة الاجتماعية)، على اعتبار أن الأسرة الحضرية لها دور  كبير في التأسيس التربوي على الحس الجمالي، وما بين ما تقوم به (المدرسة الجزائرية) من تحقيق التأهيل التربوي وتنمية الذوق الجمالي عبر تكوين خبرات جمالية جيدة لها مغزى لدى التلميذ، من خلال البيئة الصفية ومختلف المناهج والبرامج والأنشطة التربوية (الفنية والثقافية) في الفضاء المدرسي؛ مما قد تسهم في فهم وحل الكثير من الإشكلات اليومية داخل المدرسة (كمشكلة العنف المدرسي مثلا)، قد تؤسس لآليات عملية واستراتيجيات تعلميّة تساعد على بناء تلميذ متزن نفسيًّا، ومندمج اجتماعيًّا، ومتفوق دراسيًّا. الكلمات المفتاحية : التربية الجمالية، الأسرة الحضرية، المدرسة الجزائرية، التغاير النسقي، التمثلات الوالدية، التنشئة الاجتماعية. These papers deal with the issue of (aesthetic education) as a field of child education, monitoring parental representations about the aesthetic taste in the family home and in school life, and trying to reveal what we do not know about daily practices within the school and sociological analysis by linking this field to the structural change in family patterns And the extent of the importance of this field of education (aesthetic field) as a functional part in the nature of the complementary relationship between (urban family) and (school as an institution for social upbringing), considering that the urban family has a great role in the establishment of education on the aesthetic sense, (The Algerian school) to achieve educational rehabilitation and development of aesthetic taste through the formation of good aesthetic experiences of significance to the student, through the classroom environment and the various curricula and programs and educational activities (artistic and cultural) in the school space, which may contribute to understanding and solve many of the daily problems within The school (eg the problem of school violence) may establish practical mechanisms and learning strategies that help build a psychologically balanced, socially integrated and academically superior pupil. Keywords: aesthetic education, urban family, Algerian school, heterogeneity, parental representations, socialization.